European pliopithecid diets revised in the light of dental microwear in Pliopithecus canmatensis and Barberapithecus huerzeleri. Issue 4 (18th July 2013) - DeMiguel, Daniel; Alba, David M.; Moyà‐Solà, Salvador
ABSTRACT Pliopithecinae and Crouzeliinae (Primates: Pliopithecidae) are distinguished dentally by the sharper crests, more compressed cusps, larger foveae, and narrower molars of the latter. Traditionally, such differences were qualitatively related to increased folivory in crouzeliines. This was subsequently disproved by microwear and shearing crest analyses, indicating that all pliopithecids were soft‐fruit eaters, except for the more folivorous crouzeliine Barberapithecus. This seems however at odds with the occlusal morphology of the latter, intermediate between those of Pliopithecus and the more derived crouzeliine Anapithecus. To further assess dietary evolution in this group, we report results of dental microwear for two Iberian pliopithecids: Pliopithecus canmatensis, from several Abocador de Can Mata localities (11.8–11.7 Ma, MN8), and Barberapithecus huerzeleri from Castell de Barberà (ca. 11.2–10.5 Ma, MN8, or MN9). Contrary to previously published results, our analyses suggest that all pliopithecids, including Barberapithecus, had a frugivorous diet with a significant sclerocarpic component—apparently more marked in some pliopithecines (such as P. canmatensis) than in the crouzeliine Anapithecus. If our interpretation is correct, it would mean that, within the framework of a frugivorous diet with some hard‐object feeding, crouzeliine dental evolution would have been driven by selection pressures towards increased soft‐fruit consumption instead of folivory. Dental differences between pliopithecids and hominoids with a significant sclerocarpic component (i.e., orangutans) might be related to phylogenetic constraints, different food‐processing methods and/or fracture toughness of hard foods consumed. Although additional research would be required, results suggest that dietary niche partitioning played a significant role in the radiation of European pliopithecids. Am J Phys Anthropol 151:573–582, 2013. © 2013 Wiley Periodicals, Inc.